Implementasi Pendidikan Karakter Berbasis Budaya Sekolah Melalui Penerapan Sistem Boarding School di SMP IT Generasi Muslim Cendekia Lombok Tengah - shodiqin, shodiqin (An-Nahdlah: Jurnal Pendidikan Islam, 2021)
This study aims to reveal the implementation of school culture-based character education through the application of the boarding school system at the Islamic Junior High School of Islamic Cendekia Generation in Central Lombok, with the focus of research, namely: (1) character values ​​developed, (2) strategies used, ( 3) implications for student character. This research uses a qualitative approach with the type of case study research. The results of the study indicate that: 1) the character values ​​developed include: religious, disciplined, respectful, polite, social care and environmental care. 2) the strategy for implementing character education based on school culture through the application of the boarding school system at the Islamic Junior High School of the Muslim Cendekia Generation in Central Lombok includes: internalization of positive values ​​by all school members, exemplary, habituation and enforcement of discipline. 3) the implications of character education based on school culture through the application of the boarding school system at the Islamic SMP Terpadu Generasi Muslim Cendekia Central Lombok on the character of students include: implications for spiritual attitudes, implications for discipline, implications for social attitudes and implications for morals and behavior.